Social Justice and Sustainability: towards a more Inclusive Development Model - Basima Nyaz Mohsin; Ali Ayed Nasir (Indonesian Journal of Law and Economics Review, 2026)
General Background: Sustainable development has become a global framework since 1987, yet often neglects social justice's critical role in achieving comprehensive development. Specific Background: Contemporary development faces challenges including economic inequality, disproportionate climate impacts on vulnerable groups, inadequate social policies, and complex crises affecting marginalized populations. Knowledge Gap: The integration of social justice dimensions—distributive, procedural, and recognizable—into development frameworks remains insufficiently addressed in policy discourse. Aims: This article examines social justice and sustainable development interconnections, evaluates current challenges, and reviews global experiences to propose an inclusive development model. Results: Analysis reveals social justice as fundamental to sustainable development, with Sweden, Kenya, Egypt, and UAE demonstrating effective integration strategies. Novelty: The article proposes a comprehensive framework balancing economic, social, and environmental dimensions through six strategic components: strengthened social policies, legislative reforms, equitable resource distribution, diversity recognition, monitoring mechanisms, and international cooperation. Implications: Achieving 2030 Sustainable Development Goals requires systematic justice integration into policies to ensure societal cohesion, reduce inequality, and guarantee sustainable futures for current and future generations.Keywords : Social Justice, Sustainable Development, Inclusive Development Model, Economic Inequality, Environmental JusticeHighlight : Three justice dimensions enable equitable resource distribution and inclusive decision-making processes. Climate crises disproportionately affect vulnerable groups, requiring environmental justice in development strategies. Strong social policies and legislative reforms reduce inequality and enhance societal stability